Assessment of the hardness of S890QL material welded joins - Adrian Florea; Corneliu Rontescu; Ana-Maria Bogatu; Dumitru-Titi Cicic (Journal of Research and Innovation for Sustainable Society)
The need to reduce the mass of products manufactured by welding processes has led to the replacement of the basic steel materials, such as construction steels, by steels with high mechanical properties, such as hard and brittle steels. The increase of the mechanical properties but also of the alloying degree has led to a decrease in the weldability of these materials. The present paper presents the analysis of the welding possibilities with the gas metal arc welding process of S890QL steel. The paper analyzes the hardness values obtained in the case of welding technologies using two preheating temperature values (100 and 1500C) in the context of the variation of the cooling time between 800 and 5000C. The values resulting from the hardness measurements performed indicate that no significant changes in hardness occur in the characteristic areas of the weld bead, the material not being subjected to additional hardening processes. To analyze the weldability of the S890QL material, the results presented in the paper must be correlated with the results of the mechanical tests performed on the welded joints.